2013
DOI: 10.5916/jkosme.2013.37.8.855
|View full text |Cite
|
Sign up to set email alerts
|

A study of NOx performance for Cu-chabazite SCR catalysts by Sulfur poisoning and desulfation

Abstract: Small-pore Cu-chabazite SCR catalysts with high NOx conversion at low temperatures are of interest for marine diesel engines with exhaust temperatures in the range of 150 to 300℃. Unfortunately, fuels for marine diesel engines can contain a high level of sulfur of up to 1.5% by volume, which corresponds to a SO 2 level of 500 ppm in the exhaust gases for an engine operating with an A/F ratio of 50:1. This high level of SO 2 in the exhaust may have detrimental effects on the NOx performance of the Cu-chabazite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Using the Cu-chabazite SCR catalyst, Nam investigated the effect of reducing nitrogen oxides by SO 2 poisoning at low temperatures between 150 and 300 • C. The researcher was able to measure NO x reduction for two hours at 150 • C, and then again at the same temperature for another two hours. Although the reduction rate of NO x was reduced by 50% compared to the new one, it was reported that the higher temperature near to 300 • C, the effect of sulfur poisoning was almost eliminated [73].…”
Section: Marine Enginesmentioning
confidence: 82%
“…Using the Cu-chabazite SCR catalyst, Nam investigated the effect of reducing nitrogen oxides by SO 2 poisoning at low temperatures between 150 and 300 • C. The researcher was able to measure NO x reduction for two hours at 150 • C, and then again at the same temperature for another two hours. Although the reduction rate of NO x was reduced by 50% compared to the new one, it was reported that the higher temperature near to 300 • C, the effect of sulfur poisoning was almost eliminated [73].…”
Section: Marine Enginesmentioning
confidence: 82%
“…However, recent studies have shown that the capacity of SCR catalysts to significantly improve NO x reduction ability is limited because of the degradation of catalyst performance due to sulfur poisoning. Additional research on catalyst life is needed in the future [8].…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to satisfy the nitrogen oxides (NOx) regulations of marine diesel engines, some studies have examined exhaust gas after-treatment systems. [10][11][12][13][14][15] Presently, to reduce NOx emissions from large marine diesel engines, two methods are used most frequently: selective catalytic reduction (SCR) and exhaust gas recirculation (EGR) systems. EGR supplies engine exhaust gas inside the engine cylinder and reduces NOx output by lowering the combustion temperature inside the cylinder.…”
Section: Introductionmentioning
confidence: 99%